A drug repositioning success: The repositioned therapeutic applications and mechanisms of action of thalidomide. (April 2021) - Amare, Gedefaw Getnet; Meharie, Birhanu Geta; Belayneh, Yaschilal Muche
Background: Thalidomide is the most teratogenic human medicine ever marketed and was associated with birth defects in approximately 10, 000 children in the 1960s. The pharmacological effects of thalidomide are attributed to its anti-angiogenic, anti-inflammatory and modulatory effect on cytokines principally tumor necrosis factor-α, while the teratogenic effects are linked to two molecular targets, namely cereblon and tubulin. Teratogenicity is the gravest adverse effect of thalidomide depending on the dose and time of exposure. Nonetheless, with System for Thalidomide Education and Prescribing Safety program, the possibility of teratogenicity can be completely avoided. The sensitive period during pregnancy for thalidomide teratogenicity in humans is approximately 20-34 days after fertilization. Methods: Relevant articles were identified from Google scholar and PubMed (MEDLINE) using different search strategies. Conclusion: Clinical trials showed that thalidomide has been found effective in the treatment of advanced renal cancer, esophageal cancer, chemotherapy refractory endometrial cancer and pancreatic cancer, which can suggest its future therapeutic potential in cancer treatment. Thalidomide is also used in the treatment of inflammatory skin disorders and has shown promising effect in the treatment of autoimmune disorders and inflammatory bowel disease. Despite thalidomide being a renowned teratogen and neurotoxin, it has been successfully repositioned and FDA approved for the treatment of erythema nodosum leprosum and multiple myeloma under strict control.